2009
DOI: 10.1097/bpo.0b013e3181b2ba08
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Analgesia Compared With Intravenous Analgesia After Pediatric Posterior Spinal Fusion

Abstract: Level 2, randomized, controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 18 publications
4
34
0
2
Order By: Relevance
“…However, there are also complications of spinal fusion that mainly include wound complications, major medical complications which comprises procedure codes for endotracheal intubation, cardiopulmonary resuscitation, as well as mechanical ventilation, and mortality [9]. Additionally, during the spinal fusion, analgesia scheme such as patient-controlled epidural analgesia (PCEA) and patient-controlled intravenous analgesia (PCIA) are also of importance to relieve the pain of patients [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are also complications of spinal fusion that mainly include wound complications, major medical complications which comprises procedure codes for endotracheal intubation, cardiopulmonary resuscitation, as well as mechanical ventilation, and mortality [9]. Additionally, during the spinal fusion, analgesia scheme such as patient-controlled epidural analgesia (PCEA) and patient-controlled intravenous analgesia (PCIA) are also of importance to relieve the pain of patients [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, PCEA can relieve postoperative stress as well as can offer a fast recovery of intestinal activity after operations [26]. It was well-known that both PCEA and PCIA are applicable to the analgesia of spinal fusion, while there remains a controversy for the optimal method for the postoperative pain relief [12,27]. Recently, several previous studies have indicated that PCEA is more effective than PCIA for the analgesia of spinal fusion [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages were less side-effects such as nausea/vomiting [9,34,41,53,55], faster return of bowel function and oral intake [23, 48,54], faster ambulation [52], enhanced patient satisfaction and in a few studies faster hospital discharge [21].…”
Section: Epidural Analgesiamentioning
confidence: 99%
“…Some authors found that due to the frequent side-effects the epidural route could not be recommended as first line treatment for postoperative analgesia after spine surgery [24, 35,47], while more patients suffered paresthesia with placement of the catheter [25][26][27]. Failure of the epidural modality, need for temporarily or permanent discontinuation of epidural treatment and/or catheter loss while costing significantly more than systemic analgesia were additional reasons for less enthousiasm in certain studies [20,29,34].…”
Section: Epidural Analgesiamentioning
confidence: 99%
See 1 more Smart Citation